Study on Dust Hazard Levels and Dust Suppression Technologies in Cabins of Typical Mining Equipment in Large Open-Pit Coal Mines in China - Xiaoliang Jiao; Wei Zhou; Junpeng Zhu; Xinlu Zhao; Junlong Yan; Ruixin Wang; Yaning Li; Xiang Lu (Atmosphere)
As the world’s largest open-pit coal producer, China faces severe dust pollution in mining operations. Cabins of mining equipment (electric shovels, haul trucks, drills) exhibit unique micro-environmental contamination due to dual-source pollution (external infiltration and internal secondary dust generation), posing severe health risks to miners. This study focused on electric shovel cabins at the Heidaigou open-pit coal mine to address cabin dust pollution. Through analysis of dust physicochemical properties, a pollution characteristic database was established. Field measurements and statistical methods revealed temporal–spatial variation patterns of dust concentrations, quantifying occupational exposure risks and providing theoretical foundations for dust control. A novel gradient-pressurized air purification system was developed for harsh mining conditions. Key findings include the following. (1) Both coal-shovel and rock-shovel operators were exposed to Level I (mild hazard level), with rock-shovel operators approaching Level II (moderate hazard level). (2) The system reduced respirable dust concentrations from 0.313 mg/m3 to 0.208 mg/m3 (≥33.34% improvement) in coal-shovel cabins and from 0.625 mg/m3 to 0.421 mg/m3 (≥32.64% improvement) in rock-shovel cabins. These findings offer vital guidance for optimizing cabin design, improving dust control, and developing scientific management strategies, thereby effectively protecting miners’ health and ensuring operational safety.